THE CONCEPT AND DEVELOPMENT OF DIGITAL TECHNOLOGIES IN NURSING CARE (Eureka Journal of Health Sciences & Medical Innovation, 2026)
The digital transformation of nursing represents a qualitative change in the organization and provision of care that goes beyond the simple digitization of documentation. The article examines the development of digital nursing technologies (DNT) within the framework of information technology and their impact on patients, professional and non-professional caregivers, as well as medical institutions. Based on an extensive scoping review of over 19,000 materials, a holistic, nursing-focused methodology for evaluating DNT performance has been proposed, covering 47 areas of outcomes. It was found that research mainly focuses on patient-centered outcomes, while outcomes related to the quality of caregivers' lives and administrative aspects remain insufficiently studied. A special emphasis is placed on the progress of digital developments – from telemedicine and tracking to artificial intelligence systems and reinforcement of medical decisions. It is concluded that there is a need for unified assessment tools and improvement of digital skills of nurses for reliable implementation of digital developments in nursing care.
Keywords: digital technologies, digital nursing technologies, nursing care